2021
DOI: 10.1029/2021ja029138
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Parallel Electrical Conductivity in the Topside Ionosphere on Solar and Geomagnetic Activity

Abstract: The increasing amount of in-situ measurements available in the topside ionosphere may help to improve our knowledge of the physical processes occurring in the near-Earth environment, their impact in response to forcing from plasma of solar origin, and eventually elaborate mitigation strategies aimed at safely managing space and ground infrastructures (Moldwin, 2008). Among these processes, the amplification and dissipation of high-latitude current systems taking place in the ionosphere play a crucial role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 97 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…In fact, the characteristic shape of the magnetic equator and of the auroral regions stand out, and this is somewhat expected because the plasma in the topside ionosphere is generally constrained by the geomagnetic field [47]. This behavior has also been recently confirmed by Giannattasio et al [48,49] that, by using Swarm data, identified patterns in the parallel electrical conductivity (which is crucially affected by T e ) related to features of the geomagnetic field such as regions R1 and R2 [50] or the magnetic cusp [51]. They also identified variations in the parallel electrical conductivity due to MLT, QD latitude, season, solar, and geomagnetic activity.…”
Section: Statistical Trends Of Swarm-measured Electron Temperature Values and Comparison With Iri-modeled Onesmentioning
confidence: 70%
See 2 more Smart Citations
“…In fact, the characteristic shape of the magnetic equator and of the auroral regions stand out, and this is somewhat expected because the plasma in the topside ionosphere is generally constrained by the geomagnetic field [47]. This behavior has also been recently confirmed by Giannattasio et al [48,49] that, by using Swarm data, identified patterns in the parallel electrical conductivity (which is crucially affected by T e ) related to features of the geomagnetic field such as regions R1 and R2 [50] or the magnetic cusp [51]. They also identified variations in the parallel electrical conductivity due to MLT, QD latitude, season, solar, and geomagnetic activity.…”
Section: Statistical Trends Of Swarm-measured Electron Temperature Values and Comparison With Iri-modeled Onesmentioning
confidence: 70%
“…Therefore, in the absence of mechanisms that reduce the energy of precipitating particles T e is free to increase due, e.g., to energy exchanges with the nightside magnetosphere. Not surprisingly, there is an anticorrelation between N e and T e , and T e is significantly enhanced in regions of depleted N e , such as between region R2 and the main trough in the nightside winter; while, in contrast, it decreases in regions of enhanced N e due to energy loss to the ions [19,48,49,57,63]. Some studies in the past tried to establish a link between N e and T e , since N e is a major factor in electron energy loss due to the ionospheric plasma quasi-neutrality (density of ions is nearly equal to N e ).…”
Section: Statistical Trends Of Swarm-measured Electron Temperature Values and Comparison With Iri-modeled Onesmentioning
confidence: 96%
See 1 more Smart Citation
“…They found that the parallel conductivity (and so, to a larger extent, Te) generally increases in the dayside, and decreases in the nightside with solar activity. The explanation given by the authors of [46] to this effect is the following: during periods of high solar activity, the increase of Te in the nightside due to particle precipitation is balanced by a cooling due to collisions with ions, while the reduction of the EUV flux during low solar activity periods causes a strong reduction of both ion and electron densities, so also reducing the electron cooling; therefore, as a net result, a higher Te (and a higher parallel conductivity) is observed in the nightside during low solar activity. This is also observed in the ROTEI maps of Figure 3, especially when looking at the maps of 2019 and 2020, which correspond to the minimum of the last solar cycle.…”
Section: On the Rotei Solar Activity Variationmentioning
confidence: 99%
“…In this respect, the observed ROTEI behavior seems to agree with those pictures. In a very recent work, [46] investigated the statistical behavior of the electrical conductivity parallel to the Earth's magnetic field as a function of solar and geomagnetic activity by using the same approach as the authors of [31]. They found that the parallel conductivity (and so, to a larger extent, Te) generally increases in the dayside, and decreases in the nightside with solar activity.…”
Section: On the Rotei Solar Activity Variationmentioning
confidence: 99%